Rockburst mechanism and prevention technology for wide coal pillar return airway - Zhensuo Wang; Yongli Liu; ZhiXiang Song; Li Cong; Yongtao Zhu (Energy Science & Engineering)
Abstract In the Shaanxi‐Inner Mongolia region, where most mines employ wide coal pillar retention and dual entry layout techniques, mining pressure manifestations frequently occur during working face retreatment, posing significant challenges to safe and efficient coal production. Based on numerical simulation, theoretical analysis, and field test research, this study proposes a technical solution for preventing rockburst hazards in a wide coal pillar return airway. The research findings indicate the following: (a) Through numerical simulation and theoretical analysis, during the working face retreatment process, the wide coal pillar return airway exhibits a characteristic h‐pattern of high‐stress distribution, with asymmetric camelback curves appearing within the wide coal pillar, leading to significant static load concentration. When the roof breaks, the coal pillar bends excessively, and a large amount of energy is released, potentially causing instability. (b) Through the numerical simulation analysis, the stress peak value of the two sides of the return air lane of 21,103 working face decreases the most when the hole length is 15 m, the hole diameter is 150 mm and the hole distance is 1 m. (c) Implementation of drilling relief with a large diameter in the field effectively alleviates the issue of the return airway adjacent to the wide coal pillar, causing the stress peaks to shift deeper into the rock mass, this significantly reduces the risk of rockburst occurrence.